(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
This study deal with the determination of nutrients concentrations and their local-temporal variation in three estuaries on Mediterranean coast of Jableh city. The concentrations of inorganic forms of nitrogen, phosphorus and silicium, some, chlorophyll a as well as hydrological factors of water (salinity, temperature and pH) were determined. Seven marine sampling trips were performed, which covered all the seasons during the period of study between May 2016 and May 2017. Both Saqia Al-Bustan and Al-Rous estuaries recorded the highest concentrations of nitrate ions compared to the rest of the studied sites, while the third estuary (Al-Rumaila) recorded the highest concentrations of ammonium, phosphate and silicate ions. The time of spring peak varied from one estuary to another, but they shared the same timing for the autumn peak. The ratio (NO3-/PO4-3) in Saqiyat al-Bustan and al-Rous estuaries showed that phosphorous was the limiting factor for growth throughout the study months (Except for May 2016 and May 2017 regarding al-Rous estuary). As for the estuary of Rumaila River, nitrogen was the limiting factor for growth over all months of the study due to the huge sewage inputs received by this river. According to the variations between the two values of (ΣN/P) and (NO3-/PO4-3), both Saqiya al-Bustan and Rumaila estuaries are affected by a non-continuous sewage flow, while the Rous estuary is affected by a direct and continuous sewage flow. The ratio Si/No3- indicates that the Rumaila River is the richest in silicates compared to the rest of the estuaries, followed by the Rous estuary and then the Saqiyat al-Bustan estuary.